Music, Science and Natural Magic in Seventeenth-Century England - Gouk, Penelope (New Haven, CT Yale University Press, 1999)
What influence did music have in the domains of natural magic and early modern experimental science? In this highly original book, Penelope Gouk argues that developments in sixteenth-century musical practices changed English thought on science and magic in the next century. Her exploration of the relationships among these apparently separate disciplines sheds new light on the history of each.
Keywords: 17th Century (1601-1700); Music history; Cultural history; Magic; United Kingdom